52x-(25-14x)=54x+110

Simplify each term.

Combine 52 and x.

5×2-(25-14x)=54x+110

Combine x and 14.

5×2-(25-x4)=54x+110

Apply the distributive property.

5×2-25–x4=54x+110

Multiply –x4.

Multiply -1 by -1.

5×2-25+1×4=54x+110

Multiply x4 by 1.

5×2-25+x4=54x+110

5×2-25+x4=54x+110

5×2-25+x4=54x+110

To write 5×2 as a fraction with a common denominator, multiply by 22.

5×2⋅22+x4-25=54x+110

Write each expression with a common denominator of 4, by multiplying each by an appropriate factor of 1.

Multiply 5×2 and 22.

5x⋅22⋅2+x4-25=54x+110

Multiply 2 by 2.

5x⋅24+x4-25=54x+110

5x⋅24+x4-25=54x+110

Combine the numerators over the common denominator.

5x⋅2+x4-25=54x+110

Simplify each term.

Simplify the numerator.

Factor x out of 5x⋅2+x.

Factor x out of 5x⋅2.

x(5⋅2)+x4-25=54x+110

Raise x to the power of 1.

x(5⋅2)+x14-25=54x+110

Factor x out of x1.

x(5⋅2)+x⋅14-25=54x+110

Factor x out of x(5⋅2)+x⋅1.

x(5⋅2+1)4-25=54x+110

x(5⋅2+1)4-25=54x+110

Multiply 5 by 2.

x(10+1)4-25=54x+110

Add 10 and 1.

x⋅114-25=54x+110

x⋅114-25=54x+110

Move 11 to the left of x.

11×4-25=54x+110

11×4-25=54x+110

11×4-25=54x+110

Combine 54 and x.

11×4-25=5×4+110

Subtract 5×4 from both sides of the equation.

11×4-25-5×4=110

Combine fractions with similar denominators.

11x-5×4+-25=110

Subtract 5x from 11x.

6×4+-25=110

Reduce the expression 6×4 by cancelling the common factors.

Factor 2 out of 6x.

2(3x)4+-25=110

Factor 2 out of 4.

2(3x)2(2)+-25=110

Cancel the common factor.

2(3x)2⋅2+-25=110

Rewrite the expression.

3×2+-25=110

3×2+-25=110

Move the negative in front of the fraction.

3×2-25=110

3×2-25=110

Add 25 to both sides of the equation.

3×2=110+25

To write 25 as a fraction with a common denominator, multiply by 22.

3×2=110+25⋅22

Write each expression with a common denominator of 10, by multiplying each by an appropriate factor of 1.

Multiply 25 and 22.

3×2=110+2⋅25⋅2

Multiply 5 by 2.

3×2=110+2⋅210

3×2=110+2⋅210

Combine the numerators over the common denominator.

3×2=1+2⋅210

Simplify the numerator.

Multiply 2 by 2.

3×2=1+410

Add 1 and 4.

3×2=510

3×2=510

Cancel the common factor of 5 and 10.

Factor 5 out of 5.

3×2=5(1)10

Cancel the common factors.

Factor 5 out of 10.

3×2=5⋅15⋅2

Cancel the common factor.

3×2=5⋅15⋅2

Rewrite the expression.

3×2=12

3×2=12

3×2=12

3×2=12

Since the expression on each side of the equation has the same denominator, the numerators must be equal.

3x=1

Divide each term in 3x=1 by 3.

3×3=13

Cancel the common factor of 3.

Cancel the common factor.

3×3=13

Divide x by 1.

x=13

x=13

x=13

The result can be shown in multiple forms.

Exact Form:

x=13

Decimal Form:

x=0.3‾

Solve for x 5/2x-(2/5-1/4x)=5/4x+1/10